Impact of Dry Granular Flows on a Rigid Wall: Discrete and Continuum Approach. (2016) - Gabrieli, Fabio; Ceccato, Francesca
Abstract: Numerical simulations of impacts of granular flows with structures are complex because they have to take into account large deformations, large strain rates and interactions with boundaries or structures. Moreover, the material response is governed by interactions between grains, which leads to a complex rheology. Discrete methods (DEM), which apply a micromechanical approach, appears very well suited to this purpose, but they can hardly deal with large-scale problems. In contrasts, continuum methods can handle large granular volumes because they use a macroscopic approach in which the material behaviour is described by a constitutive model. The aim of this paper it to compare the results obtained by a discrete and a continuum approach in simulating the impact of a dry granular flow on a rigid wall. The problem is simulated with a DEM code and with a software based on the Material Point Method.